Development of video learning based on blender software in high school - Trirahma Novalia Putri Arfa; Misbahul Jannah; Arusman Arusman (Jurnal Geuthèë: Penelitian Multidisiplin, 2023)
Students consider the material of electric current and voltage is physics material that is difficult to understand and complicated. The difficulty lies in the learning media which only uses printed books in the process of teaching and learning activities so that it makes students difficult to understand the material of abstract electric currents and voltages. So that learning video media is needed as a learning medium besides printed books that can help students understand the material of alternating electric currents and voltages. This study aims to determine the design of learning videos based on blender software and the feasibility of learning videos based on blender software. This study uses the R&D method with the Alessi and Trollip development model with three stages including Planning Stage, Design Stage, and Development Stage. The resulting product is a learning video based on blender software on alternating electric current and voltage material and the feasibility assessment of the product is categorized into very feasible criteria in terms of the validation results of media experts with a percentage of 90.35% and the results of validation by material experts with a percentage of 93.98%, so that it is declared very feasible to be used as a learning medium.